Comparison of SARS-CoV-2 immune responses following vaccination with Comirnaty (Pfizer) and Vaxzevria (AstraZeneca) in healthy individuals with or without prior SARS-CoV-2 infection - Zdzisława Kondera-Anasz; Emilia Justyna Morawiec; Emilia Justyna Morawiec; Roksana Duszkiewicz; Filip Hajdrowski; Andrzej Wiczkowski (Frontiers in Immunology)
IntroductionThis study compares the immune responses of healthy individuals, with or without prior SARS-CoV-2 infection, following vaccination with Comirnaty (Pfizer) and Vaxzevria (AstraZeneca).MethodsA total of 134 volunteers were analyzed: 71 recipients of Comirnaty (36 with prior infection) and 63 recipients of Vaxzevria (33 with prior infection). Immune responses were assessed after the second and third doses by measuring anti-SARS-CoV-2 IgG levels and interferon-gamma (IFN-γ) production using an IGRA assay.ResultsSignificant differences were observed in IgG and IFN-γ concentrations between the vaccine groups. Higher IgG and IFN-γ levels were noted in individuals vaccinated with Comirnaty, especially after the third dose, indicating a stronger T-cell-mediated response. Prior infection enhanced immune responses, as previously infected individuals showed elevated IgG and IFN-γ levels. Hematological analysis revealed differences in immune activation patterns between vaccines, including variations in white blood cell counts, neutrophil-to-lymphocyte ratio (NLR), and platelet-to-lymphocyte ratio (PLR).DiscussionThese findings highlight distinct vaccine-induced immune responses depending on vaccine type, prior infection status, and number of doses administered. They contribute to understanding the differential immune memory elicited by mRNA-based and adenoviral vector-based vaccines and emphasize the importance of booster doses in maintaining robust immunity against SARS-CoV-2.